Pesan Dakwah Jefri Al-Bukhori di TV One - Suharmoko Suharmoko (TASAMUH: Jurnal Studi Islam, 2020)
The generation of rabbani is a generation of godliness and monotheism, and among them have resignation, patience and positive thinking. This understanding is often uttered by preachers such as Jefry al-Bukhari through various media including film and television shows. Jefry al-Bukhari uses TV media as a means simpler and more practical reason. Likewise movie, TV media is also an audiovisual media, meaning that it can be heard and seen at the same time. Most Indonesian television is used as the entertainment arena and the main source of information. In some areas, especially in Indonesia, many people spend their time watching television. If Islamic da'wah can utilize this media effectively, then automatically the spreading of da'wah will be wider and the religious impression it creates will be deeper. Actually television is a combination of radio and movie, because this media can deliver events in the form of live images with sound even with color when the event takes place. Therefore the movie deficiencies of its actuality can be covered up. In short, the uniqueness of radio and movie are gathered collectively in television and conversely the deficiencies in radio and film, on television are not found. Excluding the advantages contained in newspapers, or other printed medium that we can not find on this television. Currently, not a single second has passed without television shows both nationally and internationally with a variety of sophisticated communication devices. And there is not a single region that can be reached by this media. To the extent that this tool has transformed this big world into a large village (global village). In particular, Muslims in our country, however, have not been maximized to take advantage of this wasilah because it has been hit by the high cost that must be invested.